A Shape‐Persistent Quadruply Interlocked Giant Cage Catenane with Two Distinct Pores in the Solid State1. Issue 20 (6th April 2014) - Zhang, Gang; Presly, Oliver; White, Fraser; Oppel, Iris M.; Mastalerz, Michael
Abstract Discrete interlocked three‐dimensional structures are synthetic targets that are sometimes difficult to obtain with "classical" synthetic approaches, and dynamic covalent chemistry has been shown to be a useful method to form such interlocked structures as thermodynamically stable products. Although interlocked and defined hollow structures are found in nature, for example, in some viruses, similar structures have rarely been synthesized on a molecular level. Shape‐persistent interlocked organic cage compounds with dimensions in the nanometer regime are now accessible in high yields during crystallization through the formation of 96 covalent bonds. The interlocked molecules form an unprecedented porous material with intrinsic and extrinsic pores both in the micropore and mesopore regime.